Electron Transfer Reaction of Semicarbazide and Tetrakis (2, 2’- Bipyridine)-µ- Oxodiiron (III) Complex in Aqueous Acidic Media - I. B. Anweting; A. Adetoro; I. E. Okon; B. Myek (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to evaluate the physicochemical properties of electron transfer reaction of semicarbazide and tetrakis (2, 2’-bipyridine)-μ-oxodiiron (III) complex [Fe2O4+] in aqueous acidic media at [H+] = 0.001mol dm-3, µ = 0.3 mol dm-3(NaCl), T = 27 ± 0.5, at  λmax = 520 nm by spectrophotometric method. In the course of the reaction a mole of semicarbazide was consumed by a mole of [Fe2O4+]. The order of reaction is unity dependent on [Fe2O4+] and zero order dependent on semicabazide and is not H+  and µ dependent. Addition of cations and anions did not affect the reaction. There was no intermediate formation when a partially reacted reaction mixture and the solution of oxidant were respectively scanned within a wavelength of 400 -700nm. Absence of spectroscopic evidence of intermediate complex formation suggests that the reaction proceeds by the outer-sphere mechanistic pathway with ion pair character.